2000
DOI: 10.1177/00220345000790091301
|View full text |Cite
|
Sign up to set email alerts
|

Local and Chronic Application of PTH Accelerates Tooth Movement in Rats

Abstract: We previously reported that whereas systemic continuous infusion of parathyroid hormone (PTH) accelerated orthodontic tooth movement, systemic but intermittent injection of PTH did not increase the rate of tooth movement. Analysis of these data suggested that continuous administration of PTH could be applicable for orthodontic therapy. In the present study, we investigated whether local and chronic application of PTH(1-34) would accelerate orthodontic tooth movement. To increase the residence time of PTH in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 39 publications
(22 reference statements)
1
90
0
2
Order By: Relevance
“…Collins and Sinclair 12 reported that vitamin D 3 activated osteoclasts and rapid TM was observed. The local administration of prostaglandins, 13 osteocalcin, 14 or PTH 15 also induced orthodontic TM. However, because these drugs are rapidly flushed by blood circulation, daily systemic administration or daily local injection is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Collins and Sinclair 12 reported that vitamin D 3 activated osteoclasts and rapid TM was observed. The local administration of prostaglandins, 13 osteocalcin, 14 or PTH 15 also induced orthodontic TM. However, because these drugs are rapidly flushed by blood circulation, daily systemic administration or daily local injection is needed.…”
Section: Introductionmentioning
confidence: 99%
“…into the subperiosteal area and 1.4 times as a result of subcutaneous administration of 4 μg/100 g m.c. 10,11 However, another study by the same authors does not confirm the efficacy of intermittent therapy. 12 Long-term research on the superiority of this method over other protocols is needed, as well as clinical trials.…”
Section: Parathormonementioning
confidence: 93%
“…This mechanism is taken advantage in accelerated orthodontics to fasten the tooth movement. Soma and coworkers [55,56] conducted experiments on rats and suggested that continuous administration of PTH is applicable to accelerate orthodontic tooth movement. Three animal case control studies [55][56][57] performed on parathyroid hormone used for AOTM.…”
Section: Contemporary Status Of Surgical Methodsmentioning
confidence: 99%
“…The variation amongst the studies seems to arise from variations in frequency of application of laser, intensity of laser, and method of force application on the tooth. Six studies performed on LLLT among those five were RCTs [50-54] done on humans and one study involve d cross sectional animal study [49].Drugs: Parathyroid hormone, Vitamin D, Prostaglandins and Relaxin are the most commonly used pharmacological agents to increase the rate of tooth movement and thus decrease the treatment duration (Table 4) [55][56][57][58][59][60][61][62][63][64][65][66]. Parathyroid hormone: Calcium homeostatsis and bone remodeling in the human body are mainly regulated by parathyroid hormone (PTH).…”
mentioning
confidence: 99%